Health care professional's communication through an interpreter where language barriers exist in neonatal care: a national study - Katarina Patriksson; Helena Wigert; Marie Berg; Stefan Nilsson (BMC, 2019)
Abstract Background A number of parents in neonatal care are foreign-born and do not speak the local language, which makes communication between healthcare professionals and parents more difficult. Interpreters can be used when language barriers exist - parent interactions, medical communication and communication about the care of the child. The aim in this study was to examine healthcare professionals' use of interpreters and awareness of local guidelines for interpreted communication in neonatal care. Method A survey was distributed to all 2109 employees at all 38 neonatal units in Sweden, thus to all physicians, registered nurses and nurse assistants in active service. Data were analysed with descriptive statistics and dichotomized so the professionals were compared in groups of two using the Mantel-Haenszel Chi Square test and Fisher's Non Parametric Permutation test. Results The survey was answered by 41% (n = 858) representing all neonatal units. The study showed a difference between the professional groups in awareness of guidelines, availability of interpreters, and individual resources to communicate through an interpreter. Nurse assistants significantly lesser than registered nurses (p < .0001) were aware of guidelines concerning the use of interpreters. In emergency communications nurse assistants used authorized interpreters to a significantly lesser extent than physicians (p < .0001) and registered nurses (p < .0001). Physicians used authorized interpreters to a significantly higher extent than registered nurses (p 0.006) and non-authorized interpreters to a significantly lesser extent than registered nurses (p 0.013). In planned communications, nurse assistants used authorized interpreters to a significantly lesser extent than physicians (p < .0001) and registered nurses (p < .0001). Nurse assistants rated their ability to communicate with parents through an interpreter to a significantly lesser extent than physicians (p 0.0058) and registered nurses (p 0.0026). No other significant differences were found. Conclusion The results of the study show insufficient awareness of guidelines in all neonatal units in Sweden. Clinical implications might be to provide healthcare professionals with guidelines and training clinical skills in using interpreters and increasing the availability of interpreters by having interpreters employed by the hospital.